Contact Allergy: A Review of Current Problems from a Clinical Perspective - Uter, Wolfgang; Werfel, Thomas; White, Ian R.; Johansen, Jeanne D. (International Journal of Environmental Research and Public Health, 2018)
Contact allergy is common, affecting 27% of the general population in Europe. Original publications, including case reports, published since 2016 (inclusive) were identified with the aim of collating a full review of current problems in the field. To this end, a literature search employing methods of systematic reviewing was performed in the Medline® and Web of Science™ databases on 28 January 2018, using the search terms ("contact sensitization" or "contact allergy"). Of 446 non-duplicate publications identified by above search, 147 were excluded based on scrutiny of title, abstract and key words. Of the remaining 299 examined in full text, 291 were deemed appropriate for inclusion, and main findings were summarised in topic sections. In conclusion, diverse sources of exposures to chemicals of widely-differing types and structures, continue to induce sensitisation in man and may result in allergic contact dermatitis. Many of the chemicals are "evergreen" but others are "newcomers". Vigilance and proper investigation (patch testing) are required to detect and inform of the presence of these haptens to which our populations remain exposed.
EVALuna2:35667